Successful research-for-development partnerships: ILRI and CGIAR centers in the IGAD region - Flintan, Fiona E. (International Livestock Research Institute, 2022)
A presentation on the positive role that research can play in supporting development interventions by Fiona Flintan, in December 2022 at the EU workshop: Regional programme in livestock and pastoralism for climate change adaptation in Eastern/Horn of Africa, Movenpick Hotel, Nairobi